2016
DOI: 10.1002/cne.24048
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subcellular localization of alternative splicing variants of EFA6D, a guanine nucleotide exchange factor for Arf6, in the mouse brain

Abstract: EFA6D (guanine nucleotide exchange factor for ADP-ribosylation factor 6 [Arf6]D) is also known as EFA6R, Psd3, and HCA67. It is the fourth member of the EFA6 family with guanine nucleotide exchange activity for Arf6, a small guanosine triphosphatase (GTPase) that regulates endosomal trafficking and actin cytoskeleton remodeling. We propose a classification and nomenclature of 10 EFA6D variants deposited in the GenBank database as EFA6D1a, 1b, 1c, 1d, 1s, 2a, 2b, 2c, 2d, and 2s based on the combination of N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Previous studies using primary cultured neurons implicated the EFA6-Arf6 pathway in neuronal processes related to the formation of neural circuits, such as the formation of dendrites [26, 27] and dendritic spines [9] and axonal transport [28]. We have previously shown that three members of the EFA6 family, EFA6A, EFA6C and EFA6D, are abundantly expressed in the adult mouse brain with distinct spatiotemporal patterns [17, 19, 20, 25, 26, 29]. However, the functional significance of individual EFA6 members is unknown at the whole animal level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies using primary cultured neurons implicated the EFA6-Arf6 pathway in neuronal processes related to the formation of neural circuits, such as the formation of dendrites [26, 27] and dendritic spines [9] and axonal transport [28]. We have previously shown that three members of the EFA6 family, EFA6A, EFA6C and EFA6D, are abundantly expressed in the adult mouse brain with distinct spatiotemporal patterns [17, 19, 20, 25, 26, 29]. However, the functional significance of individual EFA6 members is unknown at the whole animal level.…”
Section: Discussionmentioning
confidence: 99%
“…First, Arf6 can be activated by several Sec7-containing Arf GEFs: EFA6A–D in the EFA6 family [16–18, 20], BRAG1–3 in the BRAG family [34, 36, 44] and cytohesin 1–3 in the cytohesin family [45, 51]. Indeed, Purkinje cells abundantly express EFA6D [29], BRAG2 (our unpublished data), BRAG3 [36] and cytohesin 1–3 [51, 52] as well as EFA6C. Although the present immunoblot analyses failed to detect any compensatory changes in the protein expression of these Arf6 GEFs, it is still possible that their subcellular localization or GEF activities may be changed in Purkinje cells lacking EFA6C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are multiple splice variants of Arf GEFs. Some differ by an entire domain, whereas others involve microexons (Ogasawara et al, 2000; Fukaya et al, 2016). The best-characterized microexon splice variants are two isoforms of cytohesin-2.…”
Section: Introductionmentioning
confidence: 99%